Delineating preliminary prospective areas of ion-adsorption rare earth deposits with stream sediments geochemical mapping in South China. (March 2023) - Han, Zhixuan; Lu, Haotian; Zhang, Bimin; Cheng, Zhizhong; Fu, Wei; Lao, Changling; Xu, Cheng
Graphical abstract: Highlights: Low density geochemical mapping is efficient of delineating potential prospecting areas of IAREDs. Positive REE anomalies are mainly associated with granitic, basaltic and carbonate rocks. More than 95% of the IAREDs are located in granitic REE anomalies. Overall, a two-step strategy for prospecting of IAREDs is proposed. Abstract: Ion-adsorption rare earth deposits (IAREDs) have received widespread attention as their indispensable supply of heavy rare earth elements (HREE), which have naturally paved the way for IAREDs exploration. However, studies on regional prospecting methods, especially geochemical methods, on IAREDs are very limited. Here, we aimed to study how to identify and delineate the potential prospecting areas of IAREDs based on 5244 sets of stream sediment geochemical data from the 76-element Geochemical Mapping (76- GEM ) project in South China at the scale of 1:2, 000, 000. The results showed that stream sediments in South China had a higher average concentration of REE (212 mg/kg) than Chinese catchment sediments (187 mg/kg) and Chinese soils (190 mg/kg), which indicated a great prospecting potentiality of IAREDs. Geochemical and geological maps revealed that the positive REE anomalies were mainly associated with three types of parent rocks: granitic, mafic igneous and carbonate rocks. Almost all IAREDs were spatially distributed in the positive REE anomalies and more than 95 % of the IAREDs were located in granitic REE anomalies. The distinct geochemical characteristics of the parent rocks, such as δEu, δCe, Eu, Si, Ca, K, Ni, Cr and Ti content, could help to distinguish REE anomalies of granitic rocks from those of mafic and carbonate rocks. Accordingly, a two-step method was proposed to prospect for IAREDs with stream sediment geochemical mapping. Overall, this study corroborated the finding that low-sampling density stream sediment geochemical mapping is an efficient method of delineating potential target areas of IARED on a national scale. But it was difficult to distinguish between LREE deposits and HREE deposits. This method showed great potential in IARED prospecting, especially in areas with a low geological degree. To the future exploration of IAREDs, the targeted multi-scale approaches for different exploration stages are essential to be developed.